STUDI ALIRAN DAYA PADA PEMODELAN SALURAN KABEL TEGANGAN TINGGI 150 KV - Hani, Slamet (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2006)
The design and operation of electrical power system, economic factor, environ-mental factor, security factor and reliability factor shoud considered. Some kinds of elec-trical power system criterion are voltage-drop and power-loss caused by peak load.The research conducts the contribution of 150 kV underground cable transmi-ssion line to increase Yogyakarta system voltage profile. A simple way to analysis some load flow study is using Electrical Transient Analysis Program ETAP Power Station 4.0.0. Applied to in PT. PLN (Persero) Jateng-DIY Sub System Region 3, 150 kV Transmission Line.The results of simulation showed that using underground cable transmission line can decrease voltage-drop rate at the power system rep to 0.74%, compared to using o-verhead transmission line which is 1.21%. Underground cable transmission line is gene-rated of reactive power by a value off 81.48% from load reactive power. So the under-ground cable transmission line contribute to decrease voltage-drop and power-loss on the electrical power system.